Emotional and psychological problems of infertility and strategies to overcome them - MR Mohammadi; F Khalajabadi Farahani (JRI, 2001)
Infertility affects women and men in reproductive ages and causes many major psychological and emotional problems. For this reason, in International Conference of Population and Development (ICPD) which was held in Cairo in 1994, infertility has been identified as a factor that has destructive effects on reproductive health. The World Health Organization (WHO) also has identified infertility as a reproductive health disturbance. The aim of this study, is evaluation of emotional and psychological problems of infertility and strategies to overcome it. In this study, some aspects of the individual or couple’s functioning have been considered which can be affected by infertility including: sexuality, self-esteem, communication, withdrawal and isolation, facing disturbing treatment process, obsession over becoming pregnant, depression, powerless, despair, exhaustion, frustration, confusion, overwhelming, anger and feeling broken. On the other hand we know psychological and emotional problems rarely can cause infertility, though these problems can be the serious effects of infertility. So attending emotional needs of the infertile couple is an integral part of infertility treatment because couple’s relationship can be affected especially when each partner needs the support and understanding of the other. Stress, frustration and embarrassment of infertility can be painful and destructive for emotional well being of the individual partners as well as for the couple’s relationship. Through analyzing the motivation of having child, can reach to some strategies of overcoming emotional and psychological problems related to infertility. Infertility as any other aspect of life is simply an event which should not be with suffering, but the majority of persons that suffer from it, find identify with it. Many basic concepts of the personal identity and the way of defining ourselves are closely associated with the capacity of having child. Psychologically, having child is a “ritual crossing to adulthood life”; it is “an essential part of the gender identity”, “ the consolidation of the couple”, “the main objective of marriage” and “the constitution of a family”. The logical conclusion that we derive from this association is I am because of my reproductive capacity and every thing it implies. If we could break this association and separate the identification between what we are and our reproductive capacity, then we see infertility with perspective, separate from what we are and see it only as an event, independent of our own value as person and in this way free ourselves from the suffering that association generates.
Keywords: Infertility, Emotional-Psychological problems, Fertility, Coping strategies